Integration of Place-Based Education for Fostering the Problem-Solving Skills of Grade 9 Students - Moyano, Nympha M.; Andrade, Rose R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Enhancing problem-solving skills is one of the primary goals of Mathematics education, however, it is still the least mastered competency among secondary learners. The primary goal of the study was to explore Place-Based Education as an innovative pedagogical approach in improving the problem-solving skills of Grade 9 students in one national high school in the Philippines. The study utilized a pre-experimental research design integrating PBE into mathematics classes. The researcher created a survey questionnaire to assess students’ level of perceptions on the integration of PBE in terms of local context, learner-centered, design-thinking, inquiry-based, community as classroom, and interdisciplinary. A researcher-made test was used to assess the pretest and posttest assessment of students’ problem-solving skills in terms of understanding the problem, planning problem-solving, problem-solving, and re-examining and conclusion. Based on the findings, students highly believed that PBE utilizes the community as a classroom, interdisciplinary, and inquiry-based. Moreover, students believed that it focuses on local context, learner-centered, and design thinking teaching approach. Furthermore, there is a significant difference in the students’ problem-solving skills before and after the experiment, thus, integration of Place-Based Education was associated with improvements in students’ problem-solving skills. The study recommends that teachers adopt the integration of PBE in the teaching-learning process in other disciplines to test other higher-order thinking skills.